The effects of Moringa Oleifera on lipid profile status, heart histology, and liver histochemistry in adult Wistar rats - Adelaja Abdulazeez Akinlolu; Elizabeth Oluwafunmilayo Bayode; Kamal Olaide Ghazali; Mubarak Oloduowo Ameen (Wolters Kluwer Medknow Publications, 2017)
Background: Moringa oleifera's leaves are globally used for nutritional and medicinal purposes. We evaluated lipid profile status, heart and liver histology, and the activities of alanine and aspartate transaminases of the liver in M. oleifera-treated adult Wistar rats. Materials and Methods: Twenty-four adult male Wistar rats were employed in the study. Rats of control Group I received physiological saline while rats of Groups II-IV received 250, 500, and 750 mg/kg bodyweight of methanolic extract of M. oleifera, respectively, for 21 days. Results: No gross morphological or behavioral anomalies were observed in rats of Groups I-IV. Histological examinations showed normal histoarchitecture of the heart in Group I and the liver of Groups I-III. Comparative histological analyses showed dose-dependent increased nucleated cells in heart tissues of rats of Groups II-IV than those of Group I. Furthermore, histological evaluations showed hypertrophy of central vein of the liver in rats of Group IV when compared to Group I. Statistical analyses showed dose-dependent nonsignificant higher mean levels (P > 0.05) of total cholesterol and triglycerides in the sera of rats of Groups II-IV compared to rats of Group I. Evaluations of levels of alanine and aspartate transaminases showed a statistically significant higher mean values (P < 0.05) in Group II, but statistically nonsignificant higher mean values (P > 0.05) in Groups III-IV compared to Group I. Conclusions: No significant adverse effects on lipid profile status, heart histology, and liver histochemistry were observed in M. oleifera-treated rats.